Microneedle structure
By using a low-melting point resin with a high weight average molecular weight and a low melting point to form a needle-shaped part of the microneedle and forming a plurality of holes on its side, the problems of insufficient strength and difficulty in removing the microneedle are solved, and more efficient drug supply is achieved and safe removal process.
Patent Information
- Application Number
- CN202380050311.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-30
- Filing Date
- 2023-06-30
- Publication Date
- 2025-02-14
AI Technical Summary
The existing microneedles are insufficient when pierced into the skin and are prone to damage, resulting in a decrease in the efficiency of the drug supply and difficulty in removing them completely, which poses a safety hazard.
A needle-shaped part is formed by a low-melting resin with a weight average molecular weight of 25,000 or more and a melting point of 130°C or less, and a plurality of holes are formed on the sides thereof to improve strength and water absorption.
The strength of the needle-like part of the microneedle is increased, damage when pierced into the skin is suppressed, the efficiency of drug supply is enhanced, and the water absorption and removal of the microneedle is promoted.
Smart Images

Figure CN119451722A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a microneedle structure. Background Art
[0002] In recent years, a technology for supplying a drug into the body and collecting body fluids from the body through a through hole formed in a microneedle has been proposed. For example, a microneedle comprising a microneedle-shaped biocompatible matrix and porous particles provided on the surface or at least a portion of the inside of the biocompatible matrix is known (Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-094171 Summary of the invention
[0006] Problems to be solved by the invention
[0007] In Patent Document 1, the biocompatible material constituting the microneedle swells or is absorbed by the biological tissue within a few seconds to a few hours when piercing the skin. Therefore, as far as the microneedle is concerned, it is assumed that it will be absorbed in the body. However, from the perspective of safety, it is desired to remove the inserted microneedle as much as possible without leaving it in the skin. Here, for example, when it is desired to remove the microneedle containing porous particles as shown in Patent Document 1 from the skin after piercing, there are problems of insufficient strength and microneedle defects. In addition, if the strength of the needle-like portion of the microneedle is low, there is a possibility that it will be damaged when piercing the skin, resulting in a decrease in the efficiency of drug supply, etc.
[0008] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide a microneedle structure having a needle-like portion with high strength.
[0009] Solutions to the problem
[0010] In order to achieve the above-mentioned object, first, the present invention provides a microneedle structure (Invention 1) having a needle-like portion having a hole formed therein, wherein:
[0011] The needle-shaped portion includes a low melting point resin having a weight average molecular weight of 25,000 or more and a melting point of 130° C. or less.
[0012] In the above invention (Invention 1), the needle-shaped portion contains a low-melting-point resin having a weight-average molecular weight of 25,000 or more and a melting point of 130°C or less, so that sufficient strength can be maintained. That is, in the case where the needle-shaped portion is a structure in which a plurality of holes are opened on its side, the speed of absorbing or releasing the fluid from the needle-shaped portion can be increased compared to a structure in which the holes are opened only at the top of the needle-shaped portion, but on the other hand, it can also be considered that the needle-shaped portion becomes brittle and sometimes lacks strength. However, in the present invention, since a low-melting-point resin having a weight-average molecular weight of 25,000 or more and a melting point of 130°C or less is contained, the strength can be increased, for example, it can be prevented from being damaged when the needle-shaped portion is inserted into the skin.
[0013] In the above invention (Invention 1), it is preferred that the needle-shaped portion contains a water-insoluble hydrophilic resin (Invention 2).
[0014] In the above invention (Invention 1), it is preferred that the water-insoluble hydrophilic resin is a water-insoluble polysaccharide (Invention 3).
[0015] In the above inventions (Inventions 1 to 3), it is preferred that a porous structure is formed in the needle-shaped portion (Invention 4).
[0016] In the above invention (Invention 4), the needle-like portion preferably has a base, and in a state where the needle-like portion is composed only of the porous structure, the water absorption rate of the needle-like portion measured by the following test method is 8.5% or more (Invention 5).
[0017] (Test method)
[0018] In an environment of 25°C, immerse the needle-shaped portion in 10 ml of purified water. Place the immersed needle-shaped portion in a reduced pressure environment of 0.09 MPa for 1 hour to allow water to penetrate into the interior of the porous structure. Next, take out the needle-shaped portion from the purified water and remove the water droplets attached to the surface. Use an air blow gun to blow away and remove the water droplets on the surface of the needle-shaped portion on the side where the needle is formed. Place the base on a glass plate, and use the dead weight of the needle-shaped portion to squeeze the water droplets around the base, thereby removing the water droplets on the surface of one side of the base of the needle-shaped portion. After standing for 5 seconds, lift the needle-shaped portion from the glass plate. Then, measure the weight of the sample after absorbing water. Then, calculate the water absorption rate (the ratio of absorbed water to the dead weight of the sample) by the following formula.
[0019] Water absorption rate (%) = (weight of sample after water absorption - weight of sample before water absorption) ÷ weight of sample before water absorption × 100
[0020] In the above invention (Invention 1), it is preferred that the needle-shaped portion contains a filler (Invention 6). BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 (1) A schematic cross-sectional view and (2) a partial enlarged view of the needle-shaped portion of the microneedle structure of the present invention.
[0022] Figure 2 This is a schematic partial cross-sectional view of a test patch using the microneedle structure of the present invention.
[0023] Figure 3 (a) to (c) are explanatory diagrams showing the steps of a method for producing a microneedle structure according to an embodiment.
[0024] Figure 4 (a) to (c) are explanatory diagrams showing the steps of a method for producing a microneedle structure according to an embodiment.
[0025] Explanation of symbols
[0026] 10 Microneedle structure
[0027] 11. Substrate
[0028] 12 Needle
[0029] 13 Hole
[0030] 14 Base
[0031] 15 Through hole
[0032] 16 Adhesive layer
[0033] 31. Solid composition
[0034] 32 protrusion
[0035] 33 Mixture DETAILED DESCRIPTION
[0036] Hereinafter, embodiments of the present invention will be described.
[0037] [Microneedle structure]
[0038] exist Figure 1 , a microneedle structure 10 according to an embodiment of the present invention is shown. The microneedle structure 10 has a plurality of needle-like portions 12 separated from each other at given intervals on one side of a substrate 11. In addition, a plurality of holes 13 are respectively formed in the needle-like portions 12. A through hole 15 is formed in the substrate 11. The microneedle structure 10 can be used as: an inspection patch that absorbs body fluids from the skin via the holes 13 of the needle-like portion 12 and uses the body fluids obtained via the substrate 11 for inspection; a drug application patch that applies drugs from the skin to the body via the holes 13 of the substrate 11 and the needle-like portion 12. It should be noted that in the present invention, body fluids include blood, lymph, interstitial fluid, etc.
[0039] (1) Needle-shaped part
[0040] The shape, size, formation spacing, and formation number of the needle-like portion 12 can be appropriately selected according to the purpose of the microneedle as the target. As the shape of the needle-like portion 12, cylindrical, prism-shaped, conical, pyramidal, etc. can be cited, and in this embodiment, it is a pyramidal shape. The maximum diameter or the maximum size of the cross section of the needle-like portion 12 can be, for example, 25 to 1000 μm, the tip diameter or the size of the cross section of the tip can be 1 to 100 μm, and the height of the needle-like portion 12 can be, for example, 50 to 2000 μm. Furthermore, the needle-like portion 12 is provided in multiple columns in one direction of the substrate 11, and multiple are formed in each column, arranged in a matrix.
[0041] The needle-shaped portion 12 is made of resin. In the present embodiment, the resin constituting the needle-shaped portion 12 is a low melting point resin, and its weight average molecular weight is 25,000 or more, that is, a high molecular weight low melting point resin. The low melting point resin refers to a thermoplastic resin, which is a resin that is solid at room temperature and has a melting point of 130°C or less. As a low melting point resin, a material with a melting point of 40 to 120°C is particularly preferred, and a material with a melting point of 45 to 100°C is most preferred. By making it solid at room temperature, the shape of the needle-shaped portion 12 can be maintained at room temperature. In addition, if the melting point is below 130°C, it is not necessary to heat at a high temperature, the cost is low and the operability is good, and even if the resin is bonded to the substrate 11 in a molten state, or the resin is heated in a state where the resin and the substrate are bonded, the substrate 11 will not soften, deform, or burn, and the degree of freedom in the selection of the substrate 11 is high. Furthermore, even when a nonwoven fabric or a resin film made of synthetic fibers with a low heat resistance temperature is used as the base material 11, deterioration of the base material 11 due to softening of the synthetic fibers can be prevented.
[0042] In addition, the weight average molecular weight of the low melting point resin is 25,000 or more, preferably 40,000 to 200,000, and more preferably 60,000 to 150,000. By being within this range, the needle-shaped portion 12 can maintain the necessary strength. In addition, by making the weight average molecular weight of the low melting point resin 25,000 or more, the water absorption of the needle-shaped portion 12 is improved. The reason for this is not necessarily clear, but it can be speculated that this is because by using a high molecular weight low melting point resin, the structure of the pore 13 possessed by the needle-shaped portion 12 is different from the case where a low molecular weight low melting point resin is used. In addition, when the weight average molecular weight of the low melting point resin is 60,000 or more, when the needle-shaped portion 12 contains a water-insoluble hydrophilic resin described later, the water absorption of the needle-shaped portion 12 can be further improved.
[0043] The tip strength of the needle-shaped portion 12 obtained by including a high molecular weight low melting point resin is usually 100 mN or more, preferably 150 mN or more, and more preferably 200 mN or more. By being 100 mN or more, even if the skin is pierced, the needle-shaped portion 12 can be prevented from being damaged with a high probability, and the microneedle structure 10 can be used for example for inspection patches, etc. The tip strength of the needle-shaped portion 12 is a value measured according to the steps described in the embodiments described later.
[0044] As described later, in the case of a structure in which a plurality of holes 13 are opened on the side of the needle-shaped portion 12, the speed of absorbing or releasing the fluid from the needle-shaped portion 12 can be increased compared to a structure in which the holes are opened only on the top of the needle-shaped portion, but on the other hand, the needle-shaped portion 12 becomes brittle and the strength is easily reduced. However, in the present embodiment, by using a low melting point resin having a weight average molecular weight of 25,000 or more to constitute the needle-shaped portion 12, the strength of the needle-shaped portion 12, in particular, the tip strength of the needle-shaped portion 12 can be increased, and for example, the needle-shaped portion 12 can be prevented from being damaged when the needle-shaped portion 12 is inserted into the skin.
[0045] The high molecular weight low melting point resin constituting the needle-shaped portion 12 can be further a water-insoluble resin. By making it water-insoluble, when applied to a biological organism, it will not be dissolved by a fluid containing water such as a body fluid, and the shape of the microneedle structure 10 can be maintained during the desired application time. In addition, as described later, a tiny hole portion 13 can be easily formed. As water-insoluble resins, polyolefin resins such as polyethylene and α-olefin copolymers, olefin copolymer resins such as ethylene-vinyl acetate copolymer resins, polyurethane elastomers, acrylic copolymer resins such as ethylene-ethyl acrylate copolymers, etc. can be cited. From the viewpoint of reducing solubility in water, it is preferred that the water-insoluble low melting point resin does not have a hydrophilic functional group such as a hydroxyl group, a carboxyl group, a sulfonic acid group, an amine group, or an acetamide group in the part other than the end.
[0046] In addition, the high molecular weight low melting point resin constituting the needle-shaped portion 12 can be further a biodegradable resin. Here, a biodegradable resin refers to a plastic that is finally completely decomposed into CO2 and water by the action of microorganisms existing in nature after use. By making it a biodegradable resin, the impact on the organism can be reduced. As such a biodegradable resin, aliphatic polyesters and their derivatives can be preferably used. In addition, homopolymers of at least one monomer selected from glycolic acid, lactic acid and caprolactone, or copolymers formed by two or more monomers can be cited. In addition, polybutylene succinate (melting point: 84-115°C), aliphatic aromatic copolyesters (melting point: 110-120°C), etc. can also be used as low melting point biodegradable resins. Specifically, as polybutylene succinate, BioPBS provided by Mitsubishi Chemical Corporation can be used, and as aliphatic aromatic copolyesters, Ecoflex manufactured by BASF can be used.
[0047] In addition, the biodegradable resin may be a resin whose monomer has an acid dissociation constant of 4 or more. By making the acid dissociation constant of the monomer 4 or more, the effect on the organism when the microneedle structure 10 is applied to the organism can be reduced. It should be noted that the acid dissociation constant of the monomer here, when the monomer is a cyclic ester, is the acid dissociation constant of the hydroxycarboxylic acid formed by the ring opening of the cyclic ester. The acid dissociation constant of the monomer is preferably above 4.0, and more preferably above 4.5. In addition, the acid dissociation constant of the monomer is preferably below 25, and more preferably below 15. As such a monomer constituting a biodegradable resin and having an acid dissociation constant of 4 or more, caprolactone can be cited. In the source monomers of the low-melting-point biodegradable resin, the structural unit having an acid dissociation constant of 4 or more of the monomer is preferably 70% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more in all structural units.
[0048] From the viewpoint of efficiently obtaining the effect of enabling resin processing at low temperatures, the ratio of the low melting point resin contained in the needle-shaped portion 12 to the total mass of the resin components is preferably 50% by mass or more, more preferably 65% by mass or more, and even more preferably 80% by mass or more. The needle-shaped portion 12 may further contain a high melting point resin having a melting point higher than 130° C. within a range that does not impair the effect of enabling resin processing at low temperatures. Examples of the high melting point resin include biodegradable resins such as polyglycolic acid (melting point: 218° C.), polylactic acid (melting point: 170° C.), and polyhydroxybutyric acid (melting point: 175° C.).
[0049] Most preferably, the resin constituting the needle-shaped portion 12 is polycaprolactone or a copolymer of caprolactone and other polymers, which is a water-insoluble, high-molecular-weight, low-melting-point resin and a biodegradable resin having an acid dissociation constant of 4 or more for a monomer.
[0050] From the viewpoint of improving the water absorption of the needle-shaped portion 12, it is preferred that the needle-shaped portion 12 contains a water-insoluble hydrophilic resin. The water-insoluble hydrophilic resin is insoluble in water and is a high molecular substance having a hydrophilic functional group. Since the water-insoluble hydrophilic resin is insoluble in water, it will not be dissolved by a fluid containing water such as body fluid when applied to a biological body, and the shape of the microneedle structure 10 can be maintained during the desired application time. In addition, by containing a water-insoluble hydrophilic resin, as described later, a tiny hole portion 13 can be easily formed in the needle-shaped portion 12. As the hydrophilic functional group, hydroxyl, carboxyl, sulfonic acid, amine, acetamide, etc. can be cited, preferably hydroxyl and carboxyl. The water-insoluble hydrophilic resin preferably has a hydrophilic functional group in the main chain or side chain. It should be noted that in the presence of counterions such as metal ions, the carboxyl group can be in the state of a carboxylate.
[0051] As the water-insoluble hydrophilic resin, a resin having both repeating units with hydrophilic functional groups and repeating units without hydrophilic functional groups can be used. However, in this case, it is preferred that the mass of the repeating units with hydrophilic functional groups accounts for more than half of the mass of the resin. It is more preferred that the water-insoluble hydrophilic resin contains a resin in which all repeating units have hydrophilic functional groups.
[0052] The equivalent weight of the hydrophilic functional group in the water-insoluble hydrophilic resin is, for example, 1500 or less, preferably 1100 or less, more preferably 900 or less, and further preferably 500 or less.
[0053] Examples of water-insoluble hydrophilic resins include completely saponified polyvinyl alcohol, water-insoluble polysaccharides such as cellulose, calcium alginate, chitin, and cross-linked hyaluronic acid, etc. Among them, water-insoluble polysaccharides of biological origin are preferred from the viewpoint of affinity for organisms, and cellulose is preferred from the viewpoint of keeping the raw material cost low.
[0054] From the viewpoint of further improving the water absorption of the needle-shaped portion 12 and facilitating the preparation of the composition for forming the needle-shaped portion 12, the amount of the water-insoluble hydrophilic resin contained in the needle-shaped portion 12 is preferably 4 parts by mass or more and 50 parts by mass or less, more preferably 5 parts by mass or more and 45 parts by mass or less, and even more preferably 15 parts by mass or more and 40 parts by mass or less, relative to 100 parts by mass of the high molecular weight low melting point resin. The water-insoluble hydrophilic resin is generally incompatible with the low melting point resin and exists in the needle-shaped portion 12 in a state separated from the low melting point resin.
[0055] The needle-shaped portion 12 may contain a filler. By making the needle-shaped portion 12 contain a filler, the mechanical strength of the needle-shaped portion 12 can be further improved. The filler is preferably contained in the resin of the needle-shaped portion 12 in a dispersed state.
[0056] The filler is preferably formed of a resin, preferably formed of one selected from a natural organic polymer or its modified product, and a biodegradable resin. The filler formed of the resin may also be a filler containing an inorganic component such as an organic / inorganic hybrid filler with an inorganic substance attached to the surface of the resin particles, but considering the effect on the organism, it is preferably formed only by a resin and an organic component, and more preferably only by a resin. As natural organic polymers, polysaccharides such as cellulose can be cited, and as fillers formed of natural organic polymers or their modified products, cellulose fibers, cellulose acetate spherical particles, etc. can be cited. As polysaccharides, the above-mentioned water-insoluble polysaccharides can be contained in the needle-shaped body 12 in the form of particles so that it functions as a filler.
[0057] As the biodegradable resin, the above-mentioned resins can be used. However, when the biodegradable resin is used as a high molecular weight low melting point resin, it is preferred to use a biodegradable resin different from the biodegradable resin. As described later, from the viewpoint of further improving the mechanical strength of the filler, a biodegradable resin having a melting point exceeding 130°C or having no melting point is preferred. Examples of such biodegradable resins include polylactic acid (melting point: 170°C), polyglycolic acid (melting point: 218°C), polyhydroxybutyric acid (melting point: 175°C), cellulose acetate diacetate (melting point: 230-300°C), etc. It should be noted that biodegradable resins such as cellulose butyrate diacetate are also modified products of natural organic polymers.
[0058] From the viewpoint of further improving the mechanical strength of the needle-shaped portion 12, the filler is preferably formed of a resin having a melting point exceeding 130°C or having no melting point. If the resin has a melting point exceeding 130°C, it is not easy to soften at a temperature near the room temperature at which the microneedle structure 10 is used. Therefore, by forming the filler from a resin having a melting point exceeding 130°C, it is easy to obtain sufficient strength of the microneedle structure 10. In addition, in the case where the filler 12 is formed of a resin having a melting point exceeding 130°C, by adding such a resin that is not easily meltable in the form of a filler, when mixed with a low-melting-point resin, a state in which the filler formed of the resin that is not easily meltable is dispersed in the composition is formed, and it is possible to mix and manufacture at a low temperature without melting, and therefore it is preferred. In addition to the above-mentioned biodegradable resins, examples of resins having a melting point exceeding 130°C or having no melting point include polypropylene (melting point: 155°C), polybutylene terephthalate (223°C), polyethylene terephthalate (melting point: 260°C), polytetrafluoroethylene (melting point: 327°C), melamine resin (melting point: none), unmodified cellulose (melting point: none), etc.
[0059] The filler is preferably formed of a resin having a glass transition temperature of 80°C or less. By forming the filler from a resin having a glass transition temperature of 80°C or less, even when the resin constituting the needle-shaped portion 12 is melted at a low temperature, the filler is easily softened during melting and easily merged with the resin constituting the needle-shaped portion 12. As a result, the strength of the manufactured needle-shaped portion 12 is easily improved. It should be noted that when the resin contained in the filler is cross-linked, the polymer having a glass transition temperature of 80°C or less is the polymer before cross-linking. As the resin having a glass transition temperature of 80°C or less, there can be mentioned: polypropylene (Tg: 0°C), polybutylene terephthalate (Tg: 50°C), polyethylene terephthalate (Tg: 69°C), polymethyl methacrylate (Tg: 60°C), polylactic acid (Tg: 60°C), polyglycolic acid (Tg: 40°C), polyhydroxybutyric acid (Tg: 15°C), etc. Among them, as described above, biodegradable resins are preferred, and polylactic acid, polyglycolic acid, polyhydroxybutyric acid, or copolymers of these polymer monomers are preferred. From the viewpoint of further improving the mechanical strength of the needle-shaped portion 12, it is also preferred that the filler is formed of a resin having a glass transition temperature of -10°C or more. The filler is more preferably formed of a resin having a glass transition temperature of 10 to 80°C, and more preferably formed of a resin having a glass transition temperature of 30 to 75°C.
[0060] The filler is preferably contained at 3 to 50% by mass, more preferably 5 to 43% by mass, and further preferably 10 to 35% by mass relative to the mass of the entire needle-shaped portion 12. If it is 50% by mass or less, it is easy to maintain the shape of the needle-shaped portion 12, and the processability during manufacturing is also improved. If it is 3% by mass or more, it is easier to improve the strength. By containing the filler in the content within this range, it is also easy to form the needle-shaped portion 12 with a desired porosity to maintain liquid permeability while improving the strength of the needle-shaped portion 12 based on the filler. In addition, two or more of the above-mentioned fillers may be contained. In this case, it is also preferred to contain the filler in such a way that the total amount of the filler is within the above-mentioned content range relative to the resin constituting the needle-shaped portion 12. In addition, in the case where the filler is a water-insoluble polysaccharide, the content of the filler as a water-insoluble polysaccharide is preferably 4 parts by mass or more and 50 parts by mass or less, more preferably 5 parts by mass or more and 45 parts by mass or less, and further preferably 15 parts by mass or more and 40 parts by mass or less relative to 100 parts by mass of the high molecular weight low melting point resin.
[0061] The shape of the filler can be plate-like (sheet-like), fibrous, spherical, irregular, etc., preferably fibrous. By making the shape of the filler fibrous, it is easy to fuse with the resin constituting the needle-shaped portion 12 in a molten state, and it is easy to improve the strength of the obtained needle-shaped portion 12, so it is preferred. As fillers having a fibrous shape, metal fiber fillers, carbon fibers, carbon nanofibers, and cellulose fibers can be mentioned. In the case where the filler is in a shape other than a fiber, for example, a spherical or irregular shape, as described above, by forming the filler from a resin having a glass transition temperature of 80°C or less, the filler can be easily fused with a low-melting-point resin. The particle size of the filler is 0.3 to 150 μm, preferably 0.5 to 125 μm, and more preferably 1 to 100 μm. By making the particle size of the filler 0.3 to 150 μm, it is easy to disperse the filler in the composition containing the low-melting-point resin, and in addition, the strength of the obtained microneedle structure 10 can be further improved. The particle size of the filler is a seven-point average of values obtained by observing the filler in the microneedle structure 10 with a scanning electron microscope (SEM) and measuring the length of the longest part of the particle. When the filler is fibrous, the particle size refers to the fiber length.
[0062] A hole portion 13 serving as a flow path for liquid circulation is formed inside the needle-shaped portion 12. One or more hole portions 13 are formed in one needle-shaped portion 12, and the hole portions 13 are open on the surface of the needle-shaped portion 12. The hole portion 13 can be formed in any form, for example, a connecting hole can be mechanically provided, and it is preferred to form a porous structure in the needle-shaped portion 12 as in the present embodiment. If the needle-shaped portion 12 is formed in a manner such that at least a portion thereof becomes a porous structure, body fluids or drug solutions can pass through the hole portion 13 of the porous structure, and therefore, it is not necessary to mechanically form a nanoscale flow path, which is preferred. In addition, since body fluids or drug solutions can flow through the entire flow path of the portion of the needle-shaped portion 12 where the porous structure is formed, the flow rate can be increased compared to the case where a simple connecting hole is formed. In the case where the needle-shaped portion 12 is formed with a porous structure, the surface area of the hole portion 13 that a fluid containing water such as a body fluid or drug solution contacts inside the needle-shaped body 12 is large. Therefore, by making the needle-shaped portion 12 contain a water-insoluble hydrophilic resin, the hydrophilicity of the surface of the hole portion 13 can be increased, thereby easily obtaining the effect of improving the water absorption of the needle-shaped portion 12. In addition, when the needle-shaped portion 12 is formed so that at least a part thereof becomes a porous structure as described above, if the porous structure is not covered on part or all of the side surface of the needle-shaped portion, the hole portion 13 is also opened on the side surface of the needle-shaped portion 12. In this case, compared with the case where the hole portion 13 is opened only at the tip of the needle-shaped portion 12, the flow rate of the liquid can be increased.
[0063] However, it is considered that the needle-shaped portion 12 becomes brittle in such a case. However, in this embodiment, since the needle-shaped portion 12 is formed using a low-melting-point resin having a weight-average molecular weight of 25,000 or more and a melting point of 130° C. or less, the needle-shaped portion 12 can be formed to have high strength without becoming brittle.
[0064] The method for forming the porous structure will be described in detail later. From the viewpoint of making the hole portion 13 a continuous structure, it is preferable to form the porous structure at the same time as the needle-shaped portion 12 is formed, or to form the protrusion 32 ( Figure 1In the latter case, for example, the protrusion 32 can be formed by mixing two or more different materials, and then at least one material can be removed to form the hole 13, thereby obtaining the needle-shaped portion 12 with a porous structure. In the case where the needle-shaped portion 12 contains a filler, according to such a method for forming a porous structure, the filler is contained in a state dispersed in the resin of the needle-shaped portion 12. In the present embodiment, the needle-shaped portion 12 is formed of high molecular weight polycaprolactone, and as described later, the protrusion 32 is made of polycaprolactone as a water-insoluble resin and a water-soluble material, and the water-soluble material soluble in water is removed in the removal step to form the hole 13, and the water-insoluble resin insoluble in water is left, thereby making the needle-shaped portion 12 with a porous structure.
[0065] Thus, the hole 13 is a gap formed by removing the water-soluble material from the protrusion 32 formed by the water-insoluble high molecular weight low melting point resin and the water-soluble material, and the body fluid and the drug solution pass through the hole 13 as a flow path. As shown in the cross section of the needle-shaped portion 12, a plurality of gaps are formed by removing the water-soluble material and are connected to each other. Through the hole 13, a flow path is formed from the surface of the needle-shaped portion 12 to one side of the substrate 11. The size of the opening of the hole 13 is determined according to the purpose of the inspection patch using the microneedle structure 10, and from the viewpoint of making it easy for the liquid to pass, the size of the opening is preferably 0.1 to 50.0 μm, more preferably 0.5 to 25.0 μm, and further preferably 1.0 to 10.0 μm. In the manufacturing process, the water-soluble material and its content are appropriately selected to achieve such an opening diameter.
[0066] It should be noted that, in the present embodiment, the water-soluble material is removed from the protrusion 32 formed of the water-insoluble high molecular weight low melting point resin and the water-soluble material to form the needle-shaped portion 12, but the present invention is not limited thereto, and a porous high molecular weight low melting point resin may be used to form the needle-shaped portion 12. In addition, a porous structure may be formed by using a foaming material or the like while forming the needle-shaped portion 12, or by sintering a particle-shaped composition containing a low melting point resin to form a porous structure.
[0067] In addition, the needle-shaped portion 12 may also have a base 14 provided at least throughout the region where the needle-shaped portion 12 is formed between the needle-shaped portion 12 and one side of the substrate 11. In the present embodiment, the base 14 is provided in a layered manner throughout one side of the substrate 11 as a whole. The base 14 serves as the base of each needle-shaped portion 12 and has a hole 13 similar to each needle-shaped portion 12. The base 14 is formed, for example, with a thickness of 0.1 to 500 μm. By having such a thickness, while improving the strength of the substrate 11, preferred adhesion can be obtained between the needle-shaped portion 12, the base 14 and the substrate 11.
[0068] The base 14 is also preferably a porous structure like the needle-shaped portion 12, and it is more preferable to use the same resin in a manner that forms the same porous structure as the needle-shaped portion 12. When the base 14 uses a porous structure, a flow path for liquid circulation is formed inside it, so there is no need to mechanically form the hole 13, and the liquid from the needle-shaped portion 12 can pass through the hole 13 of the base 14 and fill the through hole 15, which is preferred. In the present embodiment, the base 14 is formed of a high molecular weight low melting point resin that is the same as the needle-shaped portion 12, and is formed by the same process. Therefore, it is not only easy to make, but also the needle-shaped portion 12 and the substrate 11 can obtain better adhesion through the base 14, which is preferred. In addition, in the present embodiment, by setting the base 14 as a whole over one side of the substrate 11, the base 14 also exists in the part of the substrate 11 where the needle-shaped portion 12 is not formed in a state of being attached to the substrate 11, so that the strength of the microneedle structure 10 is further improved as a whole.
[0069] When the needle-like portion 12 has a porous structure and has a base 14 , the water absorption rate of the needle-like portion 12 measured by the following test method in a state where the needle-like portion 12 is composed only of the porous structure is preferably 8.5% or more.
[0070] (Test method)
[0071] In an environment of 25°C, immerse the needle-shaped part in 10 ml of purified water. Place the immersed needle-shaped part in a reduced pressure environment of 0.09 MPa for 1 hour to allow water to penetrate into the interior of the porous structure. Next, take out the needle-shaped part from the purified water and remove the water droplets attached to the surface. Use a blow gun to blow away the water droplets on the surface of the needle-shaped part on the side where the needle is formed, and remove them. Place the base on a glass plate, and use the dead weight of the needle-shaped part to squeeze the water droplets around the base, thereby removing the water droplets on the surface of the base side of the needle-shaped part. After standing for 5 seconds, lift the needle-shaped part from the glass plate. Then, measure the weight of the sample after absorbing water. Then, calculate the water absorption rate (the ratio of absorbed water to the dead weight of the sample) by the following formula.
[0072] Water absorption rate (%) = (weight of sample after water absorption - weight of sample before water absorption) ÷ weight of sample before water absorption × 100
[0073] The determination of water absorption can be specifically carried out by the method described in the embodiments described later. It should be noted that, when the microneedle structure 10 has a substrate 11 described later, the substrate 11 can be removed, and after the needle-shaped portion is made into a state consisting only of a porous structure, the water absorption can be measured in the same manner. Such a water absorption is more preferably 13% or more, further preferably 20% or more, and further preferably 28% or more. The upper limit of the water absorption is not particularly limited, and is usually about 50% or less.
[0074] (2) Base material
[0075] The needle-like portion 12 has a hole portion 13 formed therein as a flow path for liquid circulation, but as a result, the strength of the needle-like portion 12 is reduced compared to a needle-like portion without the hole portion 13. In the case where the needle-like portion 12 has a porous structure, there is a tendency for the strength of the needle-like portion 12 to be further reduced. Therefore, in the present embodiment, in order to support the needle-like portion 12 from the root side of the needle-like portion 12 to improve the strength of the microneedle structure 10, the microneedle structure 10 has a substrate 11 having a needle-like portion 12 on one side.
[0076] The substrate 11 is preferably configured so that liquid can pass through it in the thickness direction. The fact that liquid can pass through it in the thickness direction of the substrate 11 means that the substrate 11 itself can be composed of a liquid-permeable material, or the substrate 11 can be composed of a liquid-impermeable material and configured so that liquid can pass through it in the thickness direction of the substrate 11 through the through holes 15 formed in the substrate 11.
[0077] As the substrate 11 composed of a liquid-permeable material, there can be mentioned a porous substrate having microscopic substrate pores that penetrate from one side (the side provided with the needle-shaped portion 12) to the back side (the side opposite to the side provided with the needle-shaped portion 12) by interconnecting a plurality of gaps. In the case of using a low-melting-point resin as the resin for forming the needle-shaped portion 12, the composition containing the low-melting-point resin can be processed at a low temperature, thereby avoiding exposure of the substrate 11 to a high temperature. Therefore, various substrates can be selected as the substrate 11 according to the application. As such a substrate 11 composed of a liquid-permeable material, it can be in the form of a plate, preferably in the form of a sheet having high conformability to the skin. As the substrate 11, it is preferred to use a substrate formed of a fibrous substance that is easy to handle. Here, the fibrous substance in the present invention refers to fibers such as natural fibers and chemical fibers. As the substrate formed of a fibrous substance, there can be mentioned non-woven fabrics, woven fabrics, knitted fabrics, paper, etc. formed by these fibers.
[0078] In the case where the substrate 11 is made of a material having liquid impermeability and can allow liquid to pass through the through hole 15 in its thickness direction, the liquid absorption of the substrate 11 can be suppressed, so that the liquid passes only in the through hole 15 in the substrate 11. Therefore, the body fluid obtained by the needle-shaped portion 12 or the drug solution transported to the needle-shaped portion 12 will not seep into the substrate 11, and the entire amount can be circulated through the through hole 15. Thus, when the microneedle structure 10 is used as an inspection patch, the body fluid can pass through the substrate 11 immediately, so that rapid analysis can be achieved. In addition, even when the microneedle structure 10 is used as a drug administration patch, the drug solution will not seep out, and the entire amount of the drug solution can be quickly supplied to the skin. In the case where the substrate 11 has a through hole 15, as described in the international public pamphlet WO2023 / 042525, the microneedle structure 10 can be set to a structure in which an absorbent material capable of absorbing liquid is filled in the through hole, and the absorbent material can be a porous material. By configuring the microneedle structure 10 in this manner, the flow of liquid such as body fluid between the analysis sheet 17 to be described later and the drug storage unit provided on the back side of the substrate 11 and the living body can be further accelerated.
[0079] As such a material having liquid impermeability, resin films, metal-containing sheets, glass films, etc. can be cited. As a metal-containing sheet, metal foil can be cited. In addition, among resin films, a resin film having improved water resistance by forming a metal layer on a resin film with low water resistance by vapor deposition or the like can be used as a metal-containing sheet. In addition, it can be a material that does not have liquid impermeability, such as non-woven fabric, paper, etc., or a laminated resin film composed of a water-insoluble resin laminated on these materials so as to be liquid-impermeable as a whole.
[0080] In the present embodiment, the substrate 11 is formed of a liquid-impermeable resin film. As a resin for such a resin film, a resin with relatively low heat resistance selected from polybutylene terephthalate, polyethylene terephthalate, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, vinyl chloride, acrylic resin, polyurethane and polylactic acid, a heat-resistant resin such as polyimide, polyamide-imide, polyether sulfone, etc. can also be used. In the present embodiment, by using a low-melting-point resin as the resin forming the needle-shaped portion 12, the composition containing the low-melting-point resin can be processed at low temperature, thereby preventing the substrate 11 from being exposed to high temperature. Therefore, even if a resin film using a resin with low heat resistance is used, problems such as deformation of the substrate are not likely to occur.
[0081] In addition, the substrate 11 may be a single layer or a structure formed by laminating multiple layers. The substrate 11 may be a substrate formed by laminating a porous substrate 11 such as a nonwoven fabric and a liquid-impermeable substrate 11 having through holes. In addition, the resin film may be a composite film obtained by impregnating a nonwoven fabric or a cloth with a resin. The thickness of the substrate 11 is preferably 3 to 200 μm, more preferably 10 to 140 μm, and further preferably 30 to 115 μm. If the thickness is 3 μm or more, it is easy to maintain the strength of the substrate 11. In addition, if the thickness is 200 μm or less, the followability to the skin is improved and the liquid transportation time can be shortened.
[0082] For the substrate 11, an adhesive layer 16 is provided on the side where the needle-shaped portion 12 is formed. Thus, the adhesion between the needle-shaped portion 12 and the substrate 14 and the substrate 11 can be improved. As such an adhesive layer, a pressure-sensitive adhesive is preferably used, and acrylic adhesives, silicone adhesives, rubber adhesives, etc. can be cited, and acrylic adhesives can be more preferably used. In addition, by providing an adhesive layer 16 on the substrate 11, in the manufacturing method of the microneedle structure described later, the solid composition 31 is bonded to the substrate 11 in advance, and the substrate 11 and the solid composition 31 are placed in a mold, and heated and extruded in a heating and pressing process, the microneedle structure 10 can be easily obtained. In the case where the adhesive layer 16 is provided on the substrate 11, there is a hidden danger that a gap is generated between the substrate 11 and the needle-shaped portion 12, causing liquid to leak out, or that the liquid between the substrate 11 and the needle-shaped portion 12 is hindered by the adhesive layer. Therefore, it is preferred to provide the adhesive layer 16 in a manner surrounding the area through which the liquid is to pass in the substrate 11, and to provide a non-formed area of the adhesive layer 16 in the central portion. It should be noted that, although such an effect cannot be obtained, a first primer layer (not shown) may be provided instead of the adhesive layer 16 for the purpose of improving the adhesion between the needle-shaped portion 12 and the substrate 11. In addition, even if the substrate 11 has the adhesive layer 16, the first primer layer may be provided as an intermediate layer between the substrate 11 and the adhesive layer 16. Examples of the primer layer include acrylic primer layers, polyester primer layers, and the like.
[0083] As the acrylic adhesive, an acrylic adhesive containing an acrylic polymer obtained by polymerizing a monomer having an alkyl acrylate as a main component can be used. The acrylic polymer can be a copolymer of an alkyl acrylate and other monomers. As other monomers, acrylates other than alkyl acrylates such as acrylates having a hydroxyl group, acrylates having a carboxyl group, and acrylates having an ether group, and monomers other than acrylates such as vinyl acetate and styrene can be cited.
[0084] The acrylic polymer can be cross-linked by a reaction between a functional group derived from the above-mentioned acrylate having a hydroxyl group, acrylate having a carboxyl group, etc. and a cross-linking agent.
[0085] The acrylic pressure-sensitive adhesive may contain a tackifier, a plasticizer, an antistatic agent, a filler, a curable component, and the like in addition to the above-mentioned components.
[0086] As the coating liquid for obtaining the acrylic pressure-sensitive adhesive, any of a solvent-based coating liquid and an emulsion-based coating liquid can be used.
[0087] The shape of the through hole 15 formed in the substrate 11 is not particularly limited. From the perspective of generating capillary phenomena and ensuring sufficient circulation, it is preferably a structure with multiple through holes with thin diameters. As the diameter of the through hole 15, for example, the diameter is less than 2 mm, preferably 0.05 to 1 mm, and more preferably 0.1 to 0.8 mm. The method for forming the through hole 15 is not particularly limited, and for example, it can be formed by punching or laser perforation. In the present embodiment, when transporting the liquid from the needle-shaped portion 12, the substrate 11 has liquid impermeability, so the liquid will not seep into the substrate 11, and the liquid will circulate in the thickness direction of the substrate 11 through the through hole 15, so the transport distance is short, and in the case of being configured as a detection patch, it can be detected at a high analysis speed, and in the case of being configured as a drug administration patch, the drug solution can be administered at an early stage.
[0088] The total area of each through hole 15 (total area) is preferably 0.05 to 15%, more preferably 0.75 to 10%, and even more preferably 1 to 5% relative to the area of the region on the substrate 11 where the through holes 15 are provided. When the total area of the through holes 15 is 15% or less relative to the area of the above region of the substrate 11, it is easy to ensure the rigidity of the substrate 11. In addition, when the total area of the through holes 15 is 0.05% or more relative to the area of the above region of the substrate 11, body fluid can be more effectively obtained through the substrate 11.
[0089] In the case where the microneedle structure 10 is formed with a base 14, by directly bonding the base 14 to one side of the substrate 11 and forming the base 14 and the needle-shaped portion 12 integrally, the needle-shaped portion 12 can be provided on the substrate 11 without an adhesive, etc., the hole 13 is well connected, and the liquid can pass easily. Even if the microneedle structure 10 of such a configuration is not provided with an adhesive layer 16 on the substrate 11, the solid composition 31 can be bonded to the substrate 11 by heating in the formation process in the manufacturing method of the microneedle structure described later, or by a bonding method based on similar heating. It should be noted that in the present embodiment, the base 14 is provided over the entire surface of the substrate 11, but is not limited thereto. Preferably, the base 12 is formed at least in the area where the needle-shaped portion 12 is formed. Even in the case where the base 14 is directly bonded to one side of the substrate 11, a first primer layer may be provided on the substrate 11 as described above to replace the adhesive layer 16, and the base 14 may be bonded to the substrate 11 via the first primer layer, or via other layers other than the adhesive layer 16 and the first primer layer.
[0090] The microneedle structure 10 thus formed can be used as an inspection patch or a drug administration patch. Figure 2 As shown, the inspection patch 2 is provided with an analysis sheet 17 in a manner opposite to the needle-shaped portion 12 at a region where the through hole 15 is formed on the substrate 11 of the obtained microneedle structure 10, and a tape 18 is laminated in a manner covering the analysis sheet 17. In the case of a drug application patch, a drug application member is arranged in a manner opposite to the needle-shaped portion 12 at a region where the through hole 15 is formed on the covering substrate 11 of the obtained microneedle structure 10, instead of the analysis sheet 17, and a tape 18 is laminated in a manner covering the drug application member. In such an inspection patch and a drug application patch, the strength of the needle-shaped portion 12 is also high, so it is possible to pierce the skin without damaging the needle-shaped portion 12, and the constituent material of the needle-shaped portion 12 can be suppressed from remaining in the body, so it is preferred. It should be noted that the tape 18 that fixes the analysis sheet 17 or the drug application member to the substrate 11 may be an adhesive tape provided with an adhesive layer.
[0091] [Method for producing microneedle structure]
[0092] exist Figure 3 , 4The method for manufacturing the microneedle structure and the inspection patch 2 according to the embodiment of the present invention is shown in the figure. In this embodiment, a water-insoluble high molecular weight low melting point resin and a water-soluble material for forming the hole portion 13 are melted and filled into a mold (filling process), and the solid composition 31 obtained by solidifying the filled mixture is bonded to the substrate 11 (bonding process), and then the solid composition 31 is heated and pressurized to form a protrusion 32 (forming process), and then the water-soluble material is removed from the protrusion 32 (removal process), and the protrusion 32 is used as the needle-shaped portion 12. The following is a detailed description.
[0093] (Filling process)
[0094] First, the preparation of the substrate 11 and the solid composition 31 is described. First, a composition including a water-insoluble high molecular weight low melting point resin, a water-soluble material and an optional component (for example, a water-insoluble hydrophilic resin, a filler) is heated, melted and mixed to prepare a mixture 33.
[0095] In the present embodiment, the shape of the high molecular weight low melting point resin is not particularly limited, and a generally used pellet shape can be used.
[0096] When preparing the mixture 33, in the case of melting the resin, in order to reduce its viscosity, it is preferably heated at 40°C or more and 180°C or less, more preferably heated at 55-180°C, and further preferably heated at 70-170°C. In the preparation of the mixture 33, since a water-insoluble high molecular weight low melting point resin is used as the resin constituting the needle-shaped portion 12 in the present embodiment, the heating temperature can be set to be relatively low. Therefore, in the subsequent forming process, even if the substrate 11 is heated together with the solid composition 31 to form the protrusion 32, it is heated at a low temperature, so the cost is low, the operability is good, and the substrate 11 will not soften, deform, or burn, and the freedom of choice of the substrate 11 is high. In the case of using a granular high molecular weight low melting point resin, by using a mixer for mixing, the high molecular weight low melting point resin and the water-soluble material can be fully mixed. It should be noted that it is preferred that the mixture 33 is in a molten state. When emphasis is placed on heating at a lower temperature, the mixture 33 can be softened to the extent that it adheres to the substrate 11, but in consideration of reducing the manufacturing time, it is preferred to heat at a temperature above the melting point of the low-melting-point resin at which the melting of the water-insoluble material begins as described above.
[0097] As a water-soluble material, a water-soluble material having at least a higher melting point than normal temperature is preferred. The water-soluble material may be an organic substance or an inorganic substance, and examples thereof include sodium chloride, potassium chloride, sodium sulfate, sodium carbonate, potassium nitrate, alum, sugar, a water-soluble resin, and the like. As a water-soluble resin, a water-soluble thermoplastic resin is preferred, and a thermoplastic resin having a higher melting point than normal temperature is more preferred. As a water-soluble thermoplastic resin, in addition to the biodegradable resin described later, hydroxypropyl cellulose, polyvinyl pyrrolidone, and the like may be cited. Furthermore, in consideration of the impact on the human body, a water-soluble thermoplastic resin is more preferably a biodegradable resin. As such a biodegradable resin, at least one selected from polyalkylene glycols such as polyethylene glycol and polypropylene glycol, polyvinyl alcohol, collagen, and mixtures thereof may be cited, and polyalkylene glycol is particularly preferred. The molecular weight of the polyalkylene glycol is, for example, 200 to 4,000,000, more preferably 600 to 500,000, and particularly preferably 1,000 to 100,000. Among the polyalkylene glycols, polyethylene glycol is preferably used.
[0098] In addition, in order to make the high molecular weight low melting point resin and the water-soluble material easily melt at the same heating temperature when preparing the mixture 33, the difference between the melting points of the high molecular weight low melting point resin and the water-soluble material is preferably 40°C or less, more preferably 30°C or less.
[0099] The water-insoluble material and the water-soluble material are preferably mixed at a mass ratio of 9:1 to 1:9, more preferably 8.5:1.5 to 3:7, and particularly preferably 8:2 to 5:5. By forming the mixture 33 at this ratio, it is easy to form the needle-shaped portion 12 with a desired porosity, thereby achieving both liquid permeability and strength of the needle-shaped portion 12.
[0100] like Figure 3 As shown in (a), the mixture 33 is injected into a solid composition recess 42 formed in a solid composition mold (mold) 41. The solid composition recess 42 may be formed in a shape and a capacity capable of storing a desired amount of the mixture 33.
[0101] The material of the solid composition mold 41 is not particularly limited, and is preferably made of an organic silicon compound that allows for easy and accurate mold making and easy peeling of the solidified solid composition 31 . In the present embodiment, it is made of polydimethylsiloxane.
[0102] (Bonding process)
[0103] like Figure 3As shown in (b), in the state where the mixture 33 is stored in the solid composition concave portion 42, a solid composition sheet 43 formed of, for example, polydimethylsiloxane (PDMS) is placed as a cover on the upper surface of the solid composition concave portion 42 in order to flatten the surface of the obtained solid composition 31. By keeping it at -10 to 3°C for 1 to 60 minutes together with the solid composition mold 41, the molten mixture 33 solidifies and becomes solid, and therefore, it is peeled off from the solid composition mold 41 together with the solid composition sheet 43, and then the solid composition sheet 43 is peeled off. In this way, a solid composition 31 is obtained.
[0104] Prepare a substrate 11. In the present embodiment, the substrate 11 has an adhesive layer 16. The adhesive layer 16 may also be formed by coating or application. In the present embodiment, an adhesive tape having an adhesive layer 16 in a given region is used as the substrate 11. Then, a through hole 15 is formed in the substrate 11. The method for forming the through hole 15 is not particularly limited, and the through hole 15 may be formed, for example, by punching or laser perforation.
[0105] Then, if Figure 3 As shown in (c), the solid composition 31 is attached to the adhesive layer 16 of the substrate 11, so that the substrate 11 and the solid composition 31 are integrated. In this way, by having the first adhesive layer 16, the solid composition 31 is bonded to the substrate 11 in advance, the substrate 11 and the solid composition 31 are placed in a mold, and heated and pressed in the heating and pressing step described later, thereby easily obtaining the microneedle structure 10. In addition, by integrating the substrate 11 and the solid composition 31, operations such as transportation become easy.
[0106] (Formation process)
[0107] Next, if Figure 4 As shown in (a), a solid composition 31 having a substrate 11 is arranged in a recess 51 of a mold 52 having a recess 51. A recess 53 for forming a protrusion is also provided at the center of the bottom surface of the recess 51. The solid composition 31 is placed on the bottom surface of the recess 51, that is, on the recess 53 for forming a protrusion. The recess 53 for forming a protrusion is used to form the needle-shaped portion 12, and is formed in a shape and size corresponding to the needle-shaped portion 12. Then, a cover 54 of the mold 52 is provided on the other side (back side) of the substrate 11. The cover 54 is also formed of, for example, polydimethylsiloxane.
[0108] Next, proceed Figure 4(b) The heating step is used to form the protrusion 32 of the desired shape, and the heating and pressurization can be performed at one time. Preferably, as in the present embodiment, in order to fully fill the solid composition 31 into the recess 51 of the mold 52, the heating step is composed of a preliminary step and a main step, wherein the preliminary step is used to start the melting of the solid composition 31 having the substrate 11, and the main step is used to fully fill the molten solid composition 31 into the recess 51, etc.
[0109] First, in the preparatory process and the main process, Figure 4 As shown in (b), in a state where the solid composition 31 is placed in the recess 51, the substrate 11 and the solid composition 31 are clamped by the mold 52 and the cover 54. Then, in this state, the mold 52 and the cover 54 are placed on the lower stage 56, and the upper stage 57 is set above the mold 52 and the cover 54.
[0110] As the heating conditions in the preliminary process and the main process, it is sufficient to heat at a temperature of 40°C or more and 180°C or less, which has little effect on the substrate 11, preferably 55 to 180°C, and more preferably 70 to 170°C. In the present embodiment, the solid composition 31 is heated at a temperature at which it can melt. It should be noted that, for the heating of the solid composition 31, only at least one of the lower stage 56 and the upper stage 57 may be heated, or both may be heated, preferably both. In order to quickly fill the solid composition 31 containing a high molecular weight low melting point resin into the recess 51, etc., it is preferred to set the lower stage 56 to a high temperature, for example, the lower stage may be set to a temperature in the range of 120 to 180°C. As described later, from the viewpoint of obtaining the effect of improving the adhesion between the needle-shaped portion 12 or the base 14 and the substrate 11, and suppressing the deformation of the substrate caused by heat, the temperature of the upper stage 57 is preferably set to a temperature in the range of 70 to 110°C. In the main process, heating may be maintained after the preparatory process, or the temperature may be appropriately changed.
[0111] In this state, the mold 52 is squeezed (pressurized) between the upper stage 57 and the lower stage 56. The pressure in this preliminary process is preferably 0.1 to 5.0 MP. By using a pressure in this range, the solid composition 31 can be melted in a short time, and the molten solid composition 31 can be quickly filled into the recess 51, etc. Moreover, by maintaining for 10 seconds to 10 minutes, the solid composition 31 will be in a melted state. It should be noted that the pressurization conditions can be changed in the preliminary process and the main process. For example, in the main process, pressurization can be performed at a higher pressure or for a longer time than in the preliminary process.
[0112] By performing the preliminary step and the main step as in the present embodiment, the solid composition 31 can be sufficiently melted and filled into the recess 51 and the projection forming recess 53. In addition, if the obtained needle-shaped portion 12 or base 14 has a porous structure, the bonding area of the needle-shaped portion 12 or base 14 with respect to the substrate 11 becomes small, which is disadvantageous for the bonding between them. However, by heating in the forming step in a state where the substrate 11 and the solid composition 31 are bonded together, the bonding between the needle-shaped portion 12 or base 14 and the substrate 11 can be improved.
[0113] Then, the mold 52 is removed from the lower stage 37, and the molten solid composition 31 is held at -10 to 3°C for 1 to 60 minutes (refrigeration solidification step) to perform cold solidification. Thus, a protrusion 32 having a shape corresponding to the protrusion-forming recess 53 and having high transferability can be formed.
[0114] (Removal process)
[0115] After the bonding step is completed, a removal step is further performed in which the solidified material formed by bonding the protrusion 32 and the base material 11 is separated from the mold 52 and then placed in a liquid to remove the water-soluble material to form the needle-shaped portion 12 .
[0116] The cleaning liquid in the removal process includes water, and the removal process is as follows Figure 4 As shown in (c), in the present embodiment, the material formed by bonding the protrusion 32 and the substrate 11 is placed in a cleaning solution 58. By being placed in a cleaning solution containing water, the water-soluble material contained in the protrusion 32 and the like, which is exposed to the outside or communicated with the exposed part, dissolves, flows out into the water and is removed. It should be noted that the cleaning solution 58 may contain water, for example, it may be a mixed solvent of water and alcohol. By this removal, a hole portion 13 may be formed in the protrusion 32 and the like, forming a needle-shaped portion 12 formed by a residual high molecular weight low melting point resin. In addition, in addition to the needle-shaped portion 12, the water-soluble material is also removed in the molten solid composition 31 attached to one side of the substrate 11 by filling the recess 51, so that the base 14 is also formed into the same porous structure. Thus, the microneedle structure 10 of the present embodiment can be obtained.
[0117] (Inspection of manufacturing methods of patches, etc.)
[0118] The test patch 2 can be manufactured by disposing the analysis sheet 17 at a given position on the back side of the substrate 11 of the obtained microneedle structure 10 and laminating the tape 18 so as to cover the analysis sheet 17 (setting step). The lamination method can utilize a conventionally known method, for example, after placing the analysis sheet 17 on the back side of the substrate 11, the adhesive tape 18 having an adhesive layer of a rubber adhesive, an acrylic adhesive, a silicone adhesive, etc. formed on a tape substrate that is commonly used can be laminated to manufacture the test patch 2. The drug administration patch can also be manufactured by the same method.
[0119] (Variation Example)
[0120] In addition, in the present embodiment, the method of using a water-soluble material and a water-insoluble high molecular weight low melting point resin as a solid composition 31 is described, but the solid composition 31 is not particularly limited as long as it contains at least a resin. In the case of using a solid composition 31 as in the present embodiment, the composition does not contain a solvent, and therefore, the discoloration and deformation of the substrate 11 can be suppressed, and thus it is preferred. In addition, in the present embodiment, the order of the bonding process and the forming process can also be replaced, and the bonding process is performed in parallel with the forming process. That is, the mixture 33 can be filled into the recess 42, and the substrate 11 can be placed on the mixture 33 before solidifying it, and the bonding process is performed to obtain a solid composition 31 with a substrate.
[0121] In the present embodiment, in order to easily form the hole 13 by removing the water-soluble material, the needle-shaped portion 12 is formed using a water-insoluble high molecular weight low melting point resin, but as long as the above-mentioned high molecular weight low melting point resin is used, the method for making the hole 13 is not particularly limited. For example, in the formation process, a microneedle structure having a porous structure composed of a plurality of gaps between particles can be obtained by filling a particle-shaped high molecular weight low melting point resin or the like into the mold 2 and sintering at a temperature above the melting point of the low melting point resin. In this case, too, when the formation process and the bonding process are performed simultaneously, the substrate 11 has a layer formed by a heat-resistant resin, thereby suppressing the deformation and deterioration of the substrate 11. In any case, a high molecular weight low melting point resin can be used to form the needle-shaped portion 12, thereby, it is not necessary to heat at a high temperature, so the cost is low, the operability is good, and the substrate 11 will not deform / soften, which can increase the freedom of choice of the substrate 11.
[0122] In the present embodiment, in order to easily form the hole portion 13 by removing the water-soluble material, the needle-shaped portion 12 is formed using a water-insoluble material, but the method for making the needle-shaped portion 12 is not particularly limited. For example, the forming process can be based on the following method: a liquid composition containing a water-soluble material, a water-insoluble material and a solvent is formed, the above-mentioned solvent is evaporated, and the composition other than the solvent is filled in the recess for forming the protrusion, and it is dried, thereby forming the protrusion. In addition, for example, the forming process can also be based on the following method: a liquid composition is prepared in a manner so that the viscosity is 0.1 to 1000 mP·s in a state containing a water-soluble material and a water-insoluble material, and a liquid composition is dripped on the substrate 11 using a dispenser, etc., thereby forming the needle-shaped portion 12.
[0123] Example
[0124] Hereinafter, the present invention will be described in more detail with reference to examples.
[0125] It should be noted that in the embodiments and comparative examples, the weight average molecular weight (Mw) is the weight average molecular weight converted to a standard substance: polystyrene standard, measured using gel permeation chromatography (GPC) under the following conditions (GPC measurement). The preparation of the sample for GPC measurement is carried out according to the following steps. First, 1 g of polycaprolactone (PCL) used in the embodiments and comparative examples and 9 g of tetrahydrofuran (THF, manufactured by Fujifilm and Wako Pure Chemical Industries, Ltd.) were added to a screw tube, shaken to completely dissolve it, and a 10% PCL solution was prepared. Furthermore, 1 ml of the obtained solution and 9 ml of THF were added dropwise to a separately prepared screw tube to prepare a 1% PCL solution. The 1% PCL solution was filtered using a GD / X syringe filter (manufactured by Whatman) and added dropwise to the GPC device.
[0126] (Measurement conditions)
[0127] ·Measurement device: HLC-8320 manufactured by Tosoh Corporation
[0128] ·GPC column (passed in the following order): manufactured by Tosoh Corporation
[0129] TSK gel superH-H
[0130] TSK gel superHM-H
[0131] TSK gel superH2000
[0132] ·Test solvent: tetrahydrofuran
[0133] ·Measurement temperature: 40℃
[0134] (Example 1)
[0135] 3 g of polyethylene glycol (PEG) (weight average molecular weight 4000, melting point 40° C.) and 7 g of granular polycaprolactone (weight average molecular weight 80000) as a water-soluble material were heated and kneaded at 170° C. by LABO-PLASTOMILL 4C150 (Toyo Seiki Seisaku-sho, Ltd.). Thus, a mixture 33 was prepared. A mold 42 for a solid composition formed of polydimethylsiloxane was prepared, and a concave portion 42 having an opening of a square shape with each side of 15 mm×15 mm and a depth of 1.5 mm was formed in the mold 41 for the solid composition. The mixture 33 was injected in a manner that filled the concave portion 42 of the mold 41 for the solid composition.
[0136] A solid composition mold cover (a sheet formed of polydimethylsiloxane) 43 was placed on the solid composition mold 41 to flatten the surface of the solid composition 31. In this state, the molten mixture 33 was solidified and solidified by keeping it at 3°C for 5 minutes, and separated from the solid composition mold 41 to obtain a solid composition 31. Next, the adhesive layer of the substrate 11, which was an adhesive tape (an adhesive tape in which an acrylic adhesive layer (25 μm thick) was formed on a PET substrate (100 μm thick)), was bonded to the solid composition 31. Thus, a solid composition 31 having a substrate 11 was obtained.
[0137] For the forming step, a mold 52 having protrusion forming recesses 53 is prepared. The mold 52 is made of polydimethylsiloxane and has the protrusion forming recesses 53 formed on its surface having the recesses 51 as described in detail below.
[0138] ·Protrusion forming recess shape: quadrangular pyramid with a square cross section
[0139] · Length of one side of the largest cross section of the protrusion forming recess: 500 μm
[0140] ・Height of recessed portion for forming protrusion: 900μm
[0141] · Pitch of recessed portions for protrusion formation: 1000 μm
[0142] Number of recesses for forming protrusions: 13 vertical rows, 13 rows, 169 in total
[0143] ·Size of the area where the protrusion forming recess is formed: 15 mm square
[0144] ·Arrangement of recessed portions for forming protrusions: square grid shape
[0145] A mold 52 was placed on the lower stage 56 of a heating press (manufactured by AS ONE, AH-1T), and a solid composition 31 with a substrate 11 was placed on the mold 52 in a manner facing the recessed portion 51. A 30 mm square sheet (lid 54) made of polydimethylsiloxane was overlapped from above, and a preparatory process was performed by extruding at 2 MPa for 3 minutes while heating at the lower stage and the upper stage of the heating press at 140°C and 140°C. Then, the main process was performed by extruding at 4 MPa for 30 seconds while maintaining the temperature of the heating press and heating. Furthermore, the substrate 11 and the molten composition housed in the lid 54 and the mold 52 were kept in a refrigerator at 3°C for 5 minutes to solidify the composition, thereby forming a protrusion 32 and the like. Then, the substrate 11 is peeled off from the mold 52, and the substrate 11 and the formed protrusions 32 are immersed in purified water at 23°C for 24 hours to dissolve and remove the water-soluble material. Then, the substrate 11 and the molded solid composition 31 are left to stand in a drying oven (30°C) for 5 hours to evaporate the water and dry, thereby obtaining the microneedle structure 10.
[0146] (Example 2)
[0147] As the resin constituting the needle-shaped portion 12, 7 g of granular polycaprolactone (weight average molecular weight 40,000) having a molecular weight different from that in Example 1 was used, and the temperature of the heating step in the formation step was set to 110°C. A microneedle structure 10 was obtained in the same manner as in Example 1.
[0148] (Comparative Example 1)
[0149] As the resin constituting the needle-shaped portion, 7 g of granular polycaprolactone (weight average molecular weight 10,000) having a molecular weight different from that in Example 1 was used, and the temperature of the heating process in the forming process was set to 110°C. The pressurizing time of the preparatory process was further set to 1 minute and 30 seconds. Except for this, a microneedle structure was obtained in the same manner as in Example 1.
[0150] The microneedle structures obtained in Examples 1 and 2 and Comparative Example 1 were subjected to the following microneedle array transferability evaluation and microneedle tip strength evaluation.
[0151] (Evaluation of microneedle array transferability)
[0152] In each example and comparative example, the protrusions were formed by cooling the composition, and after peeling from the mold, before immersing in purified water, the protrusions were observed with an optical microscope (magnification: 50 times and 100 times), and the number of protrusions remaining on the substrate was counted. The ratio of the remaining number to the total number of protrusions in the design was calculated as the transfer rate. The case where the transfer rate was 50% or more and 100% or less was evaluated as "A", and the case where it was 0% or more and less than 50% was evaluated as "B".
[0153] (Microneedle tip strength evaluation)
[0154] The microneedle structure obtained in the embodiment and the comparative example is placed on a workbench with the needle-shaped part facing upward, and observed under a microscope. A needle-shaped body with a sharp tip shape is selected, and the attachment (iron, 2mmφ) of the measuring device (digital dynamometer (manufactured by IMADA)) is brought close to the needle-shaped part according to the position of the needle-shaped part, and care is taken not to make the attachment contact the adjacent needle-shaped part. The vertical position of the attachment is moved to a position where it contacts the tip of the needle-shaped part but does not apply force to the needle-shaped part. After rising 0.1mm from this point, the attachment is lowered at a descending speed of 5mm / min, and the force applied to the attachment (measurement range: 1 to 5000mN) is measured. At this time, the measurement temperature is 23°C and the relative humidity is 50%. On the graph outputting the measured force, the maximum value of the force displayed at the position before the force reduction is read at the moment when the force reduction is first observed, or, if the force reduction is not observed until the attachment reaches a descending distance of 100 μm, the value of the force at the moment when the attachment reaches a descending distance of 100 μm is read, and this value is used as the tip strength of the needle-shaped portion. The case where the tip strength exceeds 200 mN is evaluated as "A", the case where the tip strength is 100 to 200 mN is evaluated as "B", and the case where the tip strength is less than 100 mN is evaluated as "C". It should be noted that in the transferability evaluation, for the examples or comparative examples with a transfer rate of less than 100%, one needle-shaped portion that has not fallen off the substrate and remains is selected and evaluated.
[0155] Table 1 shows the evaluation results of Examples 1 and 2 and Comparative Example 1.
[0156] (Table 1)
[0157]
[0158] As shown in Table 1, in Examples 1 and 2 and Comparative Example 1, the microneedle array transferability was evaluated as A. On the other hand, as shown in Table 1, for the microneedle tip strength evaluation, in Comparative Example 1, the microneedle tip strength was less than 100 mN, which was evaluated as C. Thus, by using a high molecular weight (weight average molecular weight of 25,000 or more) low melting point resin, the strength of the needle-shaped portion 12 is improved.
[0159] (Example 3)
[0160] The microneedle structure 10 was obtained in the same manner as in Example 1 except that the following points were changed. The microneedle structure 10 obtained in this example did not have the substrate 11 .
[0161] The cover 54 is placed directly on the solid composition 31 without bonding the substrate 11 to the solid composition 31 .
[0162] Regarding the temperature and time of the heating process in the forming process, the lower stage of the heating press is set to a heating temperature of 115°C and the upper stage is set to a heating temperature of 105°C, and the time of the preparatory process is changed to 1 minute and 30 seconds (the time of the main process remains unchanged).
[0163] The conditions for immersing the molded solid composition 31 in purified water were changed to purified water at 40° C. for 24 hours, and the conditions for drying the molded solid composition 31 were changed to 40° C. for 24 hours.
[0164] (Example 4)
[0165] A microneedle structure 10 was obtained in the same manner as in Example 3 except that 7 g of granular polycaprolactone (weight average molecular weight 40,000) having a molecular weight different from that in Example 3 was used as the resin constituting the needle-shaped portion 12 .
[0166] (Comparative Example 2)
[0167] A microneedle structure was obtained in the same manner as in Example 3 except that 7 g of granular polycaprolactone (weight average molecular weight: 10,000) having a molecular weight different from that in Example 3 was used as the resin constituting the needle-shaped portion.
[0168] (Example 5)
[0169] When preparing the mixture 33, a microneedle structure 10 was obtained in the same manner as in Example 3 except that 0.5 g of ARBOCEL Ultrafine Cellulose (average particle size: 6-12 μm, manufactured by RETTENMAIER JAPAN) was further added as a filler composed of cellulose (a water-insoluble hydrophilic resin).
[0170] (Example 6)
[0171] A microneedle structure 10 was obtained in the same manner as in Example 5 except that the amount of filler added was changed to 2.0 g.
[0172] (Example 7)
[0173] When preparing the mixture 33, a microneedle structure 10 was obtained in the same manner as in Example 4 except that 0.5 g of ARBOCEL Ultrafine Cellulose (average particle size: 6-12 μm, manufactured by RETTENMAIER JAPAN) was further added as a filler composed of cellulose.
[0174] (Example 8)
[0175] A microneedle structure 10 was obtained in the same manner as in Example 7 except that the amount of filler added was changed to 2.0 g.
[0176] (Reference Example 1)
[0177] When preparing the mixture 33 , a microneedle structure 10 was obtained in the same manner as in Comparative Example 2 except that 0.5 g of ARBOCEL Ultrafine Cellulose (average particle size: 6-12 μm, manufactured by RETTENMAIER JAPAN) was further added as a filler composed of cellulose.
[0178] (Reference Example 2)
[0179] A microneedle structure 10 was obtained in the same manner as in Reference Example 1 except that the amount of filler added was changed to 2.0 g.
[0180] The microneedle structures (needle-shaped portions without a substrate) obtained in Examples 3 to 8, Comparative Example 2, and Reference Examples 1 and 2 were evaluated for water absorption as described below.
[0181] (Water absorption evaluation)
[0182] The weight of the sample before the needle-shaped part of the sample absorbed water was measured. Then, in an environment of 25°C, the sample was placed in a tray (manufactured by AS ONE, the balance dish was not charged), 10 ml of purified water was injected, and the sample was immersed. Then, the tray was placed in a reduced pressure environment of 0.09 MPa for 1 hour to allow water to penetrate into the porous structure of the sample. Then, the sample was taken out of the tray and the water droplets attached to the surface were removed. Specifically, the water droplets on the surface of the side where the needle of the needle-shaped part was formed were blown away and removed by a blow gun. In addition, for the water droplets on the surface of the base side of the needle-shaped part, the base was placed on a glass plate, and the water droplets were squeezed out to the surrounding of the base by the weight of the needle-shaped part. After standing for 5 seconds, the needle-shaped part was lifted from the glass plate. Then, the weight of the sample after absorbing water was measured. Then, the water absorption rate (the ratio of the absorbed water to the dead weight of the sample) was calculated by the following formula.
[0183] Water absorption rate (%) = (weight of sample after water absorption - weight of sample before water absorption) ÷ weight of sample before water absorption × 100
[0184] The evaluation results are shown in Table 2. In Table 2, the "addition amount" of the water-insoluble hydrophilic resin is a value expressing the ratio of the mass of the water-insoluble hydrophilic resin to the total mass of the low melting point resin and the water-soluble resin in percentage.
[0185] (Table 2)
[0186]
[0187] It was confirmed that the water absorption rate of Examples 3 and 2 was higher than that of Comparative Example 2, and that the higher the molecular weight of the low melting point resin, the higher the water absorption rate. In addition, in Examples 5, 6 and Examples 7, 8, the water absorption rate was significantly increased by containing cellulose, which is a water-insoluble hydrophilic resin, compared with Examples 3 and 4, which have the same molecular weight of the low melting point resin. In these cases, Examples 5 and 6, in which the weight average molecular weight of the low melting point resin was 80,000, tended to have a higher water absorption rate than Examples 7, 8 and Reference Examples 1 and 2, which contained the same amount of cellulose.
[0188] Industrial Applicability
[0189] The microneedle structure of the present invention can be used as a test patch by, for example, placing an analysis sheet on the back side and laminating the sheet with a tape.
Claims
1. A microneedle structure comprising a needle-like portion having a hole formed therein, wherein: The needle-shaped portion includes a low melting point resin having a weight average molecular weight of 25,000 or more and a melting point of 130° C. or less.
2. The microneedle structure according to claim 1, wherein The needle-shaped portion includes a water-insoluble hydrophilic resin.
3. The microneedle structure according to claim 2, wherein: The water-insoluble hydrophilic resin is a water-insoluble polysaccharide.
4. The microneedle structure according to any one of claims 1 to 3, wherein A porous structure is formed in the needle-shaped portion.
5. The microneedle structure according to claim 4, wherein The needle-shaped portion has a base, and the water absorption rate of the needle-shaped portion measured by the following test method when the needle-shaped portion is composed only of the porous structure is 8.5% or more, Test method: In an environment of 25°C, the needle-shaped part is immersed in 10 ml of purified water, and the immersed needle-shaped part is placed in a reduced pressure environment of 0.09 MPa for 1 hour to allow water to penetrate into the porous structure. Then, the needle-shaped part is taken out from the purified water, and water droplets attached to the surface are removed. The water droplets on the surface of the needle-shaped part on the side where the needle-shaped part is formed are blown away and removed by a blow gun. The base is placed on a glass plate, and the water droplets are squeezed to the periphery of the base by the self-weight of the needle-shaped part, thereby removing the water droplets on the surface of the base side of the needle-shaped part. After standing for 5 seconds, the needle-shaped part is lifted from the glass plate, and then the weight of the sample after water absorption is measured. Then, the water absorption rate (the ratio of absorbed water to the self-weight of the sample) is calculated by the following formula: Water absorption rate (%) = (weight of sample after water absorption - weight of sample before water absorption) / weight of sample before water absorption × 100.
6. The microneedle structure according to claim 1, wherein The needle-shaped portion contains a filler.
Citation Information
Patent Citations
Microneedle and microneedle array
JP2014094171A
Microneedle patch
WO2023042525A1